2003
DOI: 10.1590/s0104-66322003000100013
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of chromium (VI) by the indirect action of Thiobacillus thioparus

Abstract: The microbial reduction of chromium(VI) to chromium(III) has been one of the most widely studied forms of metal bioremediation. Recently, we have found that Thiobacillus ferrooxidans and Thiobacillus thiooxidans, growing on elemental sulphur, can indirectly promote chromium(VI) reduction by producing reducing agents such as sulphite and thiosulphate, which abiotically reduce chromium(VI). Those species of Thiobacillus are acidophilic bacteria which grow optimally at pH values lower than 4. However, most of tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…For example, chromate may act as terminal electron acceptor for gaining energy [32]. Reduction of Cr (VI) might be due to the chemical compounds like cysteine, sulphite, glutathione and thiosulfates might reduce Cr (VI) into Cr (III) [33]. The enzymatic activities of bacteria might also be one of the possible reasons for reduction of Cr (VI) by soluble and membrane-bound reductases that exist in several of aerobic, facultative and anaerobic bacteria [34].…”
Section: Resultsmentioning
confidence: 99%
“…For example, chromate may act as terminal electron acceptor for gaining energy [32]. Reduction of Cr (VI) might be due to the chemical compounds like cysteine, sulphite, glutathione and thiosulfates might reduce Cr (VI) into Cr (III) [33]. The enzymatic activities of bacteria might also be one of the possible reasons for reduction of Cr (VI) by soluble and membrane-bound reductases that exist in several of aerobic, facultative and anaerobic bacteria [34].…”
Section: Resultsmentioning
confidence: 99%
“…The tolerance limit for the discharge of Cr(VI) into inland surface water is 0.1 mg/L and in potable water is 0.05 mg/L (EPA, 1990). A wide range of physical and chemical processes are available for the removal of Cr(VI) from waste water such as electro-chemical precipitation, ultrafiltration, ion exchange, electro-dialysis, reverse osmosis, chemical precipitation, and adsorption (Jung and Shiau, 2000, Yan and Viraraghavan, 2001, Balel and Kumiawan, 2004, Donati et al, 2003. The major drawbacks with these processes are high cost, toxic sludge generation or incomplete metal removal.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that organic molecules, such as formic acid (HCOOH), can act as a strong reducing agent for the catalytic reduction of Cr VI to Cr III at Pt‐ and Pd‐based nanoparticle catalysts 9. Additionally, thiosulfate ions have also been demonstrated as reductants, albeit relatively ineffectively with conversion times of up to several days 8f. 10 Importantly, however, thiosulfate salts are a National Sanitation Foundation (NSF, a WHO collaborator) approved water treatment chemical and, unlike other reductants such as formic acid, they avoid the potential problem of decreasing the pH of the reaction solution, which can inhibit the precipitation of Cr III 10.…”
Section: Introductionmentioning
confidence: 99%